Literary Function of “Peeping” in Literary History: Between Subject and Non-subject - NAGAI, Kiyotake (Modern Japanese Literary Studies, 2022)
The character in the literary text goes through the “hole” to the other side, and by doing so becomes the protagonist. Very often, the narrative discourse spoken in the third person naturally transforms into a first-person narrative. Why is this happening? This essay will study the motif of the “holes” and the corresponding change of narrative perspectives as seen in Ukigumo, Futon, Rashomon, Yaneura no Sanposha, and Snow Country. It will analyze the historical significance and the probability of free indirect speech style. Through this essay, I would like to raise a question about the possibility of writing literary history that is not based on “author” or “canon,” that is, the history of intertextual stylistic history and expressions.